2015
DOI: 10.17795/acr-25724
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Over the Incidence of Colorectal Cancer in Iran

Abstract: Context:Colorectal cancer (CRC) is the third most prevalent cancer worldwide which is less common in the Middle East. It is also the second leading cause of cancer-related mortality and represents a major public health problem in developed countries. Objectives: The present review aimed to explore the differences among the reports on number and age standardized incidences of CRC in both sexes in different areas of Iran to find the incidence trend of this cancer. Data Sources: All the published reports citing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…Incidence rates were 10.5/100,000 (12 in men and nine in women) in Morocco (2006-2008 registry) [24] and 11/100,000 (8.7 in men and 13.4 in women) [25] [28] and Kuwait (12.7/100,000 [13.6-11.8]) [29] show almost similar incidence to our results. In contrast, incidence observed in this study were higher than those recorded in Iran in 2009 (8.5/100,000 [11.3-5.8]) [30] and in Egypt (5.4/100,000 [6-4.9]) [31].…”
Section: Discussioncontrasting
confidence: 93%
“…Incidence rates were 10.5/100,000 (12 in men and nine in women) in Morocco (2006-2008 registry) [24] and 11/100,000 (8.7 in men and 13.4 in women) [25] [28] and Kuwait (12.7/100,000 [13.6-11.8]) [29] show almost similar incidence to our results. In contrast, incidence observed in this study were higher than those recorded in Iran in 2009 (8.5/100,000 [11.3-5.8]) [30] and in Egypt (5.4/100,000 [6-4.9]) [31].…”
Section: Discussioncontrasting
confidence: 93%
“…It is also the fifth and third most frequent cancer among Iranian men and women, respectively (7). Unfortunately, the prevalence of colorectal cancer has been on the rise in Iran (8).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in graph No.1, this risk was half of that of Jordan and Arab Palestinians. According to a systematic review, the risk of CRC in Iran, especially in northern and western parts, showed a mild rise during the recent 2 decades, while several studies reported lower incidence rates from southern and eastern parts of this country (19). The southern countries of the Middle East, Oman and Yemen, showed the least risk of CRC, in both the Middle East and worldwide.…”
Section: Discussionmentioning
confidence: 99%